(untitled) (BIRDEM Medical Journal, 2012)
A three month old exclusively breast fed, immunized, male baby having presented with high continued fever for 5 days. There was no clue to any infection. It was treated as viral fever. As soon as Kawasaki Disease was suspected, on about 12th day of fever, appropriate treatment was started. The baby developed multiple coronary artery aneurysms, large pericardial effusion and a rare complication, right brachial artery thrombosis resulting in pulselessness and subsequently dry gangrene of right hand and forearm. Effusion was tapped. The baby died following amputation of the limb - probably of a major adverse cardiac event. Early diagnosis and appropriate treatment according to guidelines on time are essential for saving life of children with Kawasaki disease. Lack of awareness about the disease is a problem in our country. DOI: http://dx.doi.org/10.3329/birdem.v1i1.12392 Birdem Med J 2011; 1(1): 43-45